ANALISIS PERBEDAAN DAN KETIMPANGAN PENDIDIKAN ANTARA WILAYAH KOTA DAN PEDESAAN DI INDONESIA - Ramadhani, Chairunisa Mardiah; Syariffudin, Syariffudin; Pamulaan, Alif Bahtiar (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
Education is an awareness of creating a comfortable learning atmosphere so that students can develop the potential and character that exists within students. Education is very important because it has been agreed to be the main thing in any country, because the progress of a nation can be seen from the quality of education in that nation. However, the education system experiences several factors that cause inequality and gaps in education between cities and villages. This can happen because there are many remote areas in Indonesia that lack education due to a lack of updated information and good quality teachers, where there are several teachers who teach but do not match the teacher's abilities, causing a lack of good understanding for students. Apart from the internet and the quality of teachers, in many rural areas the schools do not have good quality structures and infrastructure and are not suitable for use so that students feel uncomfortable while studying.